Increasing coverage in mass drug administration for lymphatic filariasis elimination in an urban setting: a study of Malindi Town, Kenya. - Doris W Njomo (Public Library of Science (PLoS), 2014)
Introduction Implementation of Mass Drug Administration (MDA) in urban settings is an obstacle to Lymphatic Filariasis (LF) elimination. No urban-specific guidelines on MDA in urban areas exist. Malindi district urban area had received 4 MDA rounds by the time the current study was implemented. Programme data showed average treatment coverage of 28.4% (2011 MDA), far below recommended minimum of 65-80%. Methods To identify, design and test strategies for increased treatment coverage in urban areas, a quasi-experimental study was conducted in Malindi urban area. Three sub-locations with lowest treatment coverage in 2011 MDA were purposively selected. In the pre-test phase, 947 household heads sampled using systematic random method were interviewed for quantitative data. For qualitative data, 12 Focus Group Discussions (FGDs) with single sex adult and youth male and female groups and 3 with community drug distributors (CDDs) were conducted. Forty in-depth interviews with opinion leaders and self-administered questionnaires with District Public Health officers purposively selected were carried out. The quantitative data were analyzed using SPSS version 16 and statistical significance assessed by χ(2) test.The qualitative data were analyzed manually according to study's themes. Results and discussion The identified strategies were implemented prior to and during 2012 MDA in two sub-locations (experimental) while in the third (control), usual MDA strategies were applied. In the post-test phase, 2012 MDA coverage in experimental and control sub-locations was comparatively assessed for effect of the newly designed strategies on urban MDA. Results indicated improved treatment coverage in experimental sub-locations, 77.1% in Shella and 66.0% in Barani. Central (control) sub-location also attained high coverage, 70.4% indicating average treatment coverage of 71%. Conclusion The identified strategies contributed to increased treatment coverage in experimental sites and should be applied in urban areas. Due to closeness of sites, spillover effects may have contributed to increased coverage in the control site.